Quantification of Porphyromonas gingivalis in Plaque of Severe Chronic Periodontitis Patients Associated with Interleukin-12 Serum Level Using Real-Time Polymerase Chain Reaction - Ghasaq A. Abdulwahab (Journal of Global Pharma Technology, 2019)
Background: Periodontitis is a multifactorial polymicrobial infection in which the bacteria play a fundamental role in its initiation and progression. Porphyromonas gingivalis has been implicated as a major etiological agent causing tooth loss. Aim of the study: This study was carried out for molecular identification and quantification of Porphyromonas gingivalis in subgingival plaque samples of severe chronic periodontitis (CP) patients and healthy controls and its association with interleukine-12 serum levels. Materials and Methods: Fifty one CP patients and 45 healthy controls with age ranged from (30-50) years old, were recruited. Periodontal status was assessed based on plaque index (PLI), gingival index (GI), bleeding on probing (BOP), probing pocket depth (PPD) and clinical attachment level (CAL). Real time-Polymerase chain reaction-SYBR green technique was used to quantify Porphyromonas gingivalis from extracted DNA of dental plaque samples, while enzyme-linked immunosorbent assay (ELISA) was carried out to estimate the serum level of interleukin-12. Results: The present finding revealed that Porphyromonas gingivalis count was higher in the patients compared to the healthy controls and positively associated with all clinical parameters. As well significant increase of interleukin-12 serum level was found to be associated with severe chronic periodontitis. Interestingly, positive significant correlation between bacterial count and serum interlukin-12 level was noticed. Conclusion: A quantitative real time-polymerase chain reaction is sensitive and efficient method which permits to study specific organisms and their role in periodontal disease pathogenesis. The results of this study confirmed the earlier finding of Porphyromonas gingivalis present in significantly higher levels in CP patients. The positive association between bacterial count and interlukin-12 appear to be indicative of interactive relationship and may play a crucial role in pathogenesis of CP.Keywords: Periodontitis, Porphyromonas gingivalis, Real time-polymerase chain reaction, Interlukin-12, SYBR green.